Strategies for Strengthening Organisational Culture to Enhance Institutional Competitiveness - Ubaidillah Ubaidillah; Ismawati Ismawati (At Tadbir: Islamic Education Management Journal, 2026)
Organisational culture is one of the strategic factors that plays a role in improving the quality and competitiveness of educational institutions. However, research on strengthening organisational culture remains largely fragmented and has not yet systematically integrated the dimension of values with the mechanisms for their implementation. This study aims to analyse and synthesise various pieces of literature on organisational culture and to formulate a strategic model for strengthening organisational culture within the context of educational institutions. This study employs a literature review approach, analysing various relevant academic sources, including books and articles from national and international journals. The findings indicate that organisational culture does not directly influence the performance and competitiveness of educational institutions, but rather through mediating variables such as instructional practices, school climate and professional commitment. Furthermore, the effectiveness of organisational culture is also influenced by contextual factors such as environmental demands and institutional characteristics. Based on a synthesis of these findings, this study formulates an alignment-based model for strengthening organisational culture, comprising four key dimensions: the articulation of core values, the internalisation of values, the institutionalisation of systems, and organisational adaptation and learning, with leadership as the primary driving factor. This research makes a conceptual contribution by integrating the dimensions of values, practices and organisational systems into a single, comprehensive strategic framework. It is hoped that the resulting model will serve as a guide for educational institution managers in developing an organisational culture that is effective, adaptive and competitive in the face of the dynamic changes in the educational environment.